Studies On Reverse Tension Mechanism Of Cheese Dyeing (Daffodil International University Journal of Science and Technology, 2011)
In this paper reverse tension mechanism were observed. Soft winding is the main criteria of level yarn dyeing. One of the most vital difficulty of Dyeing a yarn package in cheese form is the density variation of the soft wounded packages themselves and also within a package. . In most cases this density variation results unlevelness of dyed package. This type of unlevel is very common for double ply yarn where the density varies significantly. A through investigation had made to suggest effective ways to achieve evenly dens package in soft winding section in a well equipped modern yarn dyeing factory. A new method termed as ‘reverse tension mechanism’ has developed to maintain even density within a package and also at packages themselves .Co-efficient of variance found near 0.3% for the new technique whereas it is more than 1% for the current system. This paper shows that the density achieved by reverse tension mechanism is very uniform at different layers of a package and also at the packages themselves than the conventional machine settings for both carded and combed cotton double ply yarn of finer and coarser count. Keywords: Reverse tension mechanism; Portion density; Package to package & within package; Unlevelness. DOI: http://dx.doi.org/10.3329/diujst.v6i2.9344 DIUJST 2011; 6(2): 42-52